2021
DOI: 10.3390/pharmaceutics13101531
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the “Upward Variation in the Reporting Odds Ratio Scores” to Detect the Signals of Drug–Drug Interactions

Abstract: The reporting odds ratio (ROR) is easy to calculate, and there have been several examples of its use because of its potential to speed up the detection of drug–drug interaction signals by using the “upward variation of ROR score.” However, since the validity of the detection method is unknown, this study followed previous studies to investigate the detection trend. The statistics models (the Ω shrinkage measure and the “upward variation of ROR score”) were compared using the verification dataset created from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Since as many models as the number of pairs of ASM were used, a Bonferroni correction was used to prevent from α risk inflation in DDI analyses, and results were presented with corrected 95% CI. As ROR scores can be inflated for combinations with fewer reports of interaction signals, 20 we decided to perform a sensitivity interaction analysis using the information component, with a similar Bonferroni correction. In disproportionality analysis, positive controls are drugs established to provoke the AE of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Since as many models as the number of pairs of ASM were used, a Bonferroni correction was used to prevent from α risk inflation in DDI analyses, and results were presented with corrected 95% CI. As ROR scores can be inflated for combinations with fewer reports of interaction signals, 20 we decided to perform a sensitivity interaction analysis using the information component, with a similar Bonferroni correction. In disproportionality analysis, positive controls are drugs established to provoke the AE of interest.…”
Section: Methodsmentioning
confidence: 99%
“…However, we recently reported that the ROR scores based on the frequency‐based statistics (definition by Susuta et al 4 ) are easily inflated; thus, the use of the “upward variation of ROR scores” to search for DDI signals increases the likelihood of false‐positive signal detection 5 . This means that the validity of the DDI signal reported by Matsuo et al is unclear.…”
mentioning
confidence: 99%
“…Although many algorithms for exploring safety signals have been reported, 3,4 the ROR is used to calculate safety signal scores for single agents, not recommended for combination therapies. 5 The Ω shrinkage measure proposed by Norén et al 6 is used by the World Health Organization Uppsala Monitoring Center (WHO-UMC), 7 and the previous study has shown that it has the most conservative signal detection trend among signal detection methods based on frequentist statistics. 8 Since the original article 1 does not provide detailed data on the number of reports, I could not calculate Ω shrinkage measure scores and validate the ROR score for the DDI signals between ICIs and bevacizumab.…”
mentioning
confidence: 99%
“…I reported that the ROR scores based on the frequencybased statistics were easily inflated; thus, using the "upward variation of ROR scores" to search for DDI signals increases the likelihood of false-positive signal detection. 5 Since the "odds ratio of combination therapy to monotherapy" in the original article approximates the "upward variation score of the ROR score," it is difficult to exclude the possibility that false-positive signals are included. They perform multivariate logistic regression (MLR) analysis to ascertain whether combination therapy is an independent risk factor for ADRs.…”
mentioning
confidence: 99%